The Association Between Cancer and Dementia: A National Cohort Study in Sweden - Sun, Ming; Wang, Youxin; Sundquist, Jan; Sundquist, Kristina; Ji, Jianguang (Frontiers in Oncology, 2020)
Background: Previous studies have found that the incidence of dementia is lower in patients with cancer. However, the impact of survival bias, as well as the confounding by medical treatment, have not been fully addressed. We aimed to explore the subsequent risk of dementia in different follow-up intervals among patients with cancer, as well as the risk before the diagnosis of cancer. Methods: By using the Swedish Cancer Register and the Swedish Hospital Discharge Register, we systematically examined the risk of dementia among patients diagnosed with 35 different types of cancer. Standardized incidence ratios (SIRs) were used to calculate the relative risk. Results: The subsequent risk of dementia in patients with cancer decreased by 21% compared to matched cancer-free controls (SIR=0.79, 95% CI 0.78-0.80). For specific cancer sites, 21 of them had a significantly lower risk of subsequent dementia. The decreased risk of dementia was also significant before the diagnosis of cancer. However, the risk was higher among patients with cancer who survived for more than 10 years post-diagnosis (SIR=1.37, 95% CI 1.32-1.41). Conclusions: In this population-based study, we found that the risk of dementia was lower among patients with cancer, and the risk was also lower before the diagnosis of cancer. This suggests that lower dementia risk is not simply due to bias. The biological pathway might associate with the decreased risk of dementia.